The Influence Of Capital Intensity, Company Size, Growth Opportunity, Tax On Accounting Conservatism With Leverage As Moderating Variable On Food And Beverage Company Listed In Bursa Efek Indonesia - Jhon Boris Clinton Saragih; Iskandar Muda; Rujiman (Institute of Computer Science (IOCS), 2022)
The objective of this research is to find out the influence of financial performance of Accounting Conservatism in the companies of Food and Beverages sector listed in BEI (Indonesia Stock Exchange). Independent variables are capital intensity, company size, growth opportunities and tax with conservatism accounting as dependent variable while leverage as moderating variable. The samples are 15 companies in the food and beverages companies listed in BEI in the period of 2010-2019. The datas are financial statement from each research sample published through www.idx.co.id and www.financeyahoo.com which were analyzed by quantitative method with classic assumption, multiple linear regression analysis using random effect model, taken by using purposive sampling technique. The result of analysis show that financial ratio IM partially has positive and significant influence, GO has negative and significant influence while UP and P do not have any significant influence on accounting conservatism. The variable of leverage is only able to moderate UP.